Fuzzy Logic and Analytical Hierarchy Process –AHP in the evaluation of environmental quality of sources - Silva Junior, Celso Henrique Leite; Freire, Ana Talita Galvão; Mendes, Jonas Jansen (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This study aimed to evaluate the environmental quality of the river Bacanga sources using a methodology rarely used in these types of studies, the Fuzzy Theory. In calculating the Environmental Quality Index of Sources, for the weighting of parameters was used the AHP (Analytical Hierarchical Process). As a result, the 11 sources analyzed 5 sources were framed in class A with Environmental Quality Best, 3 sources were framed in class B with Environmental Quality Good, 2 sources were framed in class C with Environmental Quality Reasonable and 1 source framed in class D with Environmental Quality Poor, no source was framed in class E with Environmental Quality Rubbish. The use of Fuzzy Logic with AHP demonstrated to be efficient in the classification of sources. The sources classified in the C and D classes require mitigation measures for the environmental recovery of the same. Urbanization was identified as the main agent of degradation of the studied sources.